Hypercalcaemia associated with chronic viral hepatitis. Issue 767 (September 1989) - Cadranel, J. F.; Cadranel, J.; Buffet, C.; Ink, O.; Pelletier, G.; Bismuth, E.; Etienne, J. P.
Abstract : A patient with long lasting non-parathyroid hormone mediated hypercalcaemia occurring within the context of hepatitis B virus chronic hepatitis is reported. Hepatocellular carcinoma and bone malignancy were carefully excluded. The biological pattern associated hypercalcaemia with normal phosphataemia, low nephrogenic cAMP level and high level of tubular reabsorption of phosphate. The usual causes of hypercalcaemia were ruled out. Hypercalcaemia may represent a rare biological feature of some advanced liver disease. The underlying mechanisms remain to be elucidated.